Communication Ethics In Surah Al-Luqman Verse 13 SolutionTo Generation Gap In The Family - Roni Apriadi (ASTEEC, 2023)
The role of parents in a family is very important, especially for the future of their children. Because after all, parents are the first madrasa that will shape the personality of their children, then how to build harmonious family relationships in the midst of the rampant term Generation Gap. The method in this study uses the library method (Librery Reasearch), which is a data collection technique by conducting a study of books, journals, and other literature that has a relationship with related issues. The results of this study reveal that the communication ethics contained in surah al-lukman verse 13 include patience, courtesy and using good words etc., so as to be able to make harmonious relationships in a family and to prevent the occurrence of Generation Gap.